# Which is a solution to (x - 3)(x + 9) = -27?

x = - 9, x = - 3, x = 0, x = 6

**Solution: **

Given:

Equation is (x - 3)(x + 9) = -27

On solving we get,

⇒ x^{2} + 9x - 3x - 27 = -27

⇒ x^{2} + 6x = 0

⇒ x(x + 6) = 0

⇒ x = 0 and x + 6 = 0

⇒ x = 0 and x = -6

We can understand by the given example below:

**Example: **

What is the solution of m^{2} - 9 = 0?

Given equation is m^{2} - 9 = 0

⇒ m^{2} = 9

⇒ Applying square root on both sides

⇒ √m^{2} = √9

⇒ m = √(3)(3)

⇒ m = ±3

⇒ m = 3 and m = -3

⇒ The factors are (m - 3) and (m + 3)

## Which is a solution to (x - 3)(x + 9) = - 27?

**Summary: **

The solution to the equation (x - 3)(x + 9) = -27 is x = 0 and x = -6.

Math worksheets and

visual curriculum

visual curriculum